"The Collective Defense of Democracy in the Americas within the Principle of Non-Intervention. The Limits of Collective Action", by Alexander Antialón Conde - Peruana de Derecho Internacional, Sociedad (2020)
This study is divided into two chapters. The first of them, covering approximatelytwo thirds focuses on the principle of non-intervention. Starting from a timelycomparative table of articles 2 of the Charter of the United Nations and 3 of the Charterof the OAS, which enunciate the fundamental principles of both Organizations, the authorundertakes the concept of non-intervention, discusses its normative background anddoctrines, in an order that I would personally reverse, presents the kinds of intervention,particularly the one related to the protection of human rights, points out the numerouscases of violation of the principle following the teaching of the Legal CommitteeInter-American and examines, finally, the cases in which the International Court of Justicehas spoken on the matter.